The Relationship Between Leisure Activity and Life Satisfaction Among Gen Z Individuals Who Enjoy Staycations - Graciela Jesusia; Rahmah Hastuti (Jurnal Indonesia Sosial Sains, 2026)
This research aims to examine the relationship between leisure activity (LA) and life satisfaction (LS) to understand the factors that contribute to the well-being of Generation Z. The research subjects consisted of 159 Generation Z individuals who enjoy staycations and were analyzed using the Leisure Satisfaction Scale and the Satisfaction with Life Scale through a correlational quantitative approach. The data analysis technique used was Spearman’s rho correlation because the data were not normally distributed. The results indicate a positive and significant relationship between the two variables, with a correlation coefficient of (). These findings suggest that the higher the quality and frequency of leisure activities, the higher the level of life satisfaction experienced by the participants. Therefore, leisure activity and staycations are proven to be important elements in maintaining the subjective well-being of Generation Z. This study is expected to raise public awareness of the importance of leisure time to enhance life satisfaction.